Control allocation strategies for an electric vehicle with a wheel hub motor failure. (2015) - Wanner, Daniel; Wallmark, Oskar; Jonasson, Mats; Drugge, Lars; Trigell, Annika Stensson
Three fault-tolerant control strategies for electric vehicles with wheel hub motors are presented and compared, which are all based on the control allocation principle. The main objective is to maintain the directional stability of the vehicle in case of a component failure during high speed manoeuvres. Two simplified strategies that are suited for on-board implementation are derived and compared to an optimal control allocation strategy and a reference vehicle with a basic electronic stability control system. The occurring faults are considered to be in the electric high-voltage system that can arise in wheel hub motors. All three control allocation strategies show improved re-allocation of traction forces after a severe fault, and hence an improved directional stability. However, the performance of both simplified algorithms shows limitations in case of force demands outside the capabilities of the respective actuator. This work shows that vehicle safety is increased by the proposed fault-tolerant control strategies.